Corpus of Śāradā inscriptions of Kashmir : with special reference to origin and development of Śāradā script - Kaul Deambi, B. K. (Bhushan Kumar), 1937- (Agam, 1982)
Study of inscriptions in Śāradā script used for writing Sanskrit and vernaculars in Kashmir.